Democratic Republic of the Congo : 2015 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Democratic Republic of the Congo. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2015)
This 2015 Article IV Consultation highlights that the Democratic Republic of the Congo's macroeconomic performance remained strong through the first half of 2015 despite a difficult external and domestic environment. Real GDP growth in 2014 is estimated at 9.2 percent, driven by copper production and the service sector. The medium-term outlook is favorable but subject to downside risks. Real GDP growth is projected to remain strong at 9.2 percent in 2015-among the highest rates in the world-and average 8.4 percent in 2016-17 before stabilizing at about 6 percent in 2018-20.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet